Analisa Keuangan Usaha Mikro Kecil Menengah (UMKM) Produsen Makanan Tahu - Imam Baidlowi (Bisman (Bisnis dan Manajemen): The Journal of Business and Management, 2022)
Finance is a very important part of a business, because the company will be able to run well and normally if the company's finances run normally. Regarding company finances, in this study researchers have conducted research related to the method of managing company finances in SMEs, traditional tofu food producers "Gono Tahu". The results of the study indicate that the traditional tofu food producer "Gono Tahu" has not carried out financial management properly according to the company's financial management standards. Therefore, it is necessary to improve the quality of human resources, especially in the financial sector. It is hoped that the Mojokerto Regency Government will make efforts to foster so that people who have micro, small and medium businesses can increase their business.